Lower Cervical and Upper Thoracic Mobilisation in the Horse. Manual Therapies are Dose Dependent and an Increase in Patient Mass is Normally Associated with an Increase in Dose. - Ahern , Tom (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Numerous manual therapy techniques have been developed to deal with musculoskeletal pain, stiffness and associated spinal joint restrictions or loss of range of movement. Cervical vertebral mobilisation under anaesthetic was one of these. It was specifically developed to deliver an adequate and maintained dose or pressure when attempting to restore lost range of movement in the lower cervical and upper thoracic joint complexes of the horse. There was however a perceived reluctance amongst clinicians to explore this approach. They understandably preferred to utilise modalities that they were more comfortable with even though these were less likely to deliver a therapeutic dose.